ENSINO DA MATEMÁTICA FINANCEIRA PARA JOVENS E ADULTOS - FÁBIO ROGÉRIO FARDIN (2021)
We live in a sad reality in the country, namely, millions of Brazilians have their names registered in credit protection agencies, such as SCPC and SERASA. This is not just because these people are poor payers, but because they lack a financial education as they enter adulthood. Another point that must be highlighted concerns the fact that, many times, by ignoring the financial traps embedded in loan operations, many people are in the hands of credit lending agents, whether officials or not. Another aggravating factor is the inadequate consumption, whether of goods or services, and consumption without need harms purchasing power. This work was aimed at high school, seeking to improve the education of young people through financial mathematics. We try to describe real cases in which a wrong decision can harm a person for a long period of life. Additionally, we highlight in this work practical examples involved in financial situations such as: interest, amortization tables, forms of payments and especially equivalence of capital, which is how money behaves over time. Keywords: Interest, rate, financing, amortization, financial mathematics, decision-making.